Recent Improvements in Gene Regulations and Immunology - Akintayo, ‎Daniel Oluwatobi; Salam, Babatunde Ridwan; Adeniran, Adetayo Olaniyi (Biocompounds, 2024)
The possibility of employing genetically altered cells as therapeutic agents have been firmly proven by the effectiveness of Chimeric Antigen Receptor (CAR) T cell treatment against haematological tumours. Even while cell therapy has made significant strides, its entire range of advantageous uses is yet unknown. The ability to apply genetic control circuits, which permits varied signal detecting and logical processing for the best response in the intricate tumour microenvironment, is one of the special benefits of cell treatments. We will first discuss design factors for cell therapy control circuits that meet clinical requirements from this angle. After contrasting and comparing important aspects of some of the most recent advancements in control circuit design, we'll talk about possible future paths.